Assessing the Role of Spatial Rainfall Variability on Watershed Response based on Weather Radar Data (A Case Study of the Gard Region, France) - Evi Anggraheni; Dwita Sutjiningsih; Isabelle Emmanuel; Olivier Payrastre; Herve Andrieu (International Journal of Technology, 2018)
The primary input for hydrological the hydrological model is rainfall. The accurate illustration of rainfall in time and space is important for rainfall-runoff modeling since it impact the hydrological responses. The impact of spatial rainfall variability on runoff representation depends on the type of rainfall, the catchment characteristic (nature and scale), and rainfall distribution. Many researchers have been observing the influence of spatial rainfall variability since 40 years ago, however the contradictive result still obtained.In order to analyze the influence of spatial rainfall variability, the distributed model CINECAR has been chosen in this research to accommodate the watershed behavior. The simulation used weather radar data with 1x1 km2 resolution. Production function of the CINECAR model adopt the Soil Conservation Service-Curve Number that take into account the soil characteristic, land use and soil moisture. The kinematic wave model is used to transfer the runoff flow system using the Saint-Venant equation. The aim of the first simulation was to confirm the performance of the CINECAR model. Secondly the comparison between average and distributed hydrograph was done to analyze the influence of spatial variability according to proposes indexes value. The objective of this paper is to confirm and analyze the impact of rainfall spatial variability in the specific context of flash floods. Secondly is to evaluate the relevance of theoretical indexes of rainfall spatial variability proposed by (D. Zoccatelli, 2010) and (I. Emmanuel, 2015). Those indexes could be used to identify situations for which rainfall spatial variability may have an influence on the watershed response and to precise the interest of distributed hydrological modeling.